HOW TRUST AND QUALITY OF INFORMATION AFFECT BUYING INTEREST AND PURCHASING DECISIONS? (study on Shopee customers in Samarinda) - Mochamad Ridwan; Theresia Militina; Gusti Norlitaria Achmad (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
This study aims to determine the effect of confidence (trust) and Quality Information and Decision on Interest Buy Pebelian (Studies in Samarinda Shopee customers). Online shopping How to use the Internet through computers and mobile devices is increasingly popular smartphone can even be said to have become the trend of today. The population in this study is the customer who Shopee samarinda use application Shopee in transacting online, The samples in this study as many as 150 respondents. Methods Data collection is done by providing a list of questions or questionnaires to respondents that the study sample, where questionnaires were distributed through WhatApp application. This study uses data analysis tools is to test the validity and reliability test, then this research analysis method of partial least square (PLS). The tools used in processing the data using PLS Smart program Research results show that 1) Belief positive and significant impact on the buying interest of customers Shopee Samarinda, 2) trust has a positive effect but not significant to purchasing decisions of customers Shopee Samarinda, 3) Quality of information about positive and significant effect on the buying interest of customers Shopee Samarinda, 4) Quality of information about positive and significant effect to the purchasing decision of customers Shopee Samarinda, 5) buying interest and significant positive effect on customer purchasing decisions Shopee Samarinda,